The Ability to Use Technology on ASN Performance Moderated By WFH During the Pandemic - Nirta Vera Yustanti; Yesi Indian Ariska; Heru Kreshna Reza; Kurniati Karim; Melly Susanti (International Journal of Educational Research & Social Sciences, 2021)
COVID19 has changed many work arrangements and cultures such as Work From Home (WFH). The government enforces a policy for all State Civil Apparatus (ASN) to work from home. The purpose of this study was to determine the ability to understand and use technology during the pandemic which was moderated by WFH in increasing the performance of the ASN in Kepahiang Regency during the COVID 19 pandemic. This study used a quantitative descriptive analysis method with multiple regression methods, namely to provide an overview about the ability to understand and use technology on the performance of ASN which is moderated by work from home. The population in this study was 145 civil servants in the government of Kepahiang Regency. Samples were taken as many as 90 ASN who had filled out the questionnaire correctly and completely. The results showed that there was an increase in the value of R Square by 0.705 (0.714-0.009) or an increase in the effect before and after WFH by 70.5%. This means that the performance of ASN (Y) has increased after the government in Kepahiang Regency implemented the policy of the head ASNto work at home during the pandemic. Prior to the policy for the WFH by the government,the performance of ASN only 9%. With the moderating variable (Work From Home) can strengthen the influence of the variable Ability to understand and use (X1) on the performance of ASN (Y). So it can be concluded that the "Hypothesis is Accepted" so that it can be said that the existence of a moderating variable or Work From Home (WFH) can strengthen or increase the influence of the ASN Performance variable (Y) in the Kepahiang Regency Government.